On the characterization of the integers the hidden function problem revisited - Berghammer Rudolf (1993)
In this paper the hidden function problem studied so far only for equational (e.g., in [9] and [ll]) or conditional equational (e.g., in [3]) algebraic specifications is considered for arbitrary first-order theories. It is shown that a unique characterization of the integers with zero, successor and predecessor as term-generated model of a finite first-order theory needs at least one hidden function or relation.
Keywords: Természettudományok; Számítás- és információtudomány